The Effect of Different Types of Climates on the Spread of COVID-19 - Farhangnasab, Mohammadamin; Pourhossein, Behzad; Golahdouz, Mahsa; Taherizadeh, Mahsa; Sharifi, Sara; Rostami, Narges; Morovati Moez, Narjes; Mahouti, Mehran; Fazeli, Maryam (Novelty in Biomedicine, 2022)
Coronavirus disease of 2019 (COVID-19) is the third most common zoonotic disease caused by the coronavirus virus, SARS in 2002, and Middle East Respiratory Syndrome (MERS) in 2012. The primary origin of transmission of infection to humans is not well known. However, more prevalence of the disease is caused due to human-to-human transmission. There are relatively few studies on the impact of climate change on COVID- 19 disease in the world. Recognizing the behavioral features of the SARS-CoV-2 virus and its pathogenicity in various climatic conditions can offer strategies for control measures, preventing the transmission of the disease, and minimizing the potential mortality risk of the virus, which provides a basis for more detailed studies in different climatic regions. This study aimed to evaluate the effect of different types of climate on the spread of COVID-19.